Penetapan Kerangka Kerja Social Crm Berdasarkan Karakteristik Media Sosial - Prasetyo, Koko Wahyu (SMATIKA, 2013)
This research is conducted to analyze and construct a framework for customer relationship management (CRM) practices implementation based on various characteristics of online social media. The framework could be used to analyze the Social CRM domains of social customer insights, marketing, sales, service and support, innovations, collaborations, and customer experiences. It will then be implemented based on prioritization analysis of organizationâs activities as well as the maturity of technologies that could support Social CRM implementation within the organization. The framework is expected to produce implementation roadmap for 5 categories of Social CRM practices as well as the relevant social media based on defined priorities of the organization.